A Review on Impact of Productivity and Quality of Welds Produced by The Submerged ARC Welding Process - Upendra Kumar; Lokesh Singh (International Journal of Scientific Research in Mechanical and Materials Engineering, 2024)
Submerged Arc Welding (SAW) process gives more benefits over conventional arc welding processes (viz. better quality, productivity, coverage of different materials/shapes/sizes). SAW is used to deposit more than 10% of the weld metal all over the world. But the need and the pressure to find more effective welding techniques, to enhance the overall productivity, to make high-quality defect-free welds and to improve the welding cost economy is increasing every day. In this research work we investigation to find, ascertain and quantify improvements in the Weld quality in bead size and flexibility of using a wider range of parameters in a wire size.
Keywords: Submerged Arc Welding; Quality; Productivity; Bead size; Wire size